Dukungan Sosial dan Psychological Adjusment pada Narapidana Wanita - Triska Amalia Sari; Dwi Hurrriyati (Ilmu Psikologi Universitas Yudharta Pasuruan, 2022)
The life that prisoners live while in prison, makes them face various psychological problems, including loss of family, loss of self-control, loss of model, and loss of support, of course, in facing various psychological problems and problems to be able to survive with these conditions while serving a sentence. In this study, the aim of this study was to determine the relationship between social support and psychological adjustment. The characteristics possessed in this study are prisoners who are first entered in prison with a detention period of 0-6 months. The method used by the researcher is quantitative with purposive random sampling technique. The sample in this study amounted to 140 prisoners, including 40 prisoners as a trial try out, and 100 prisoners as research. The results of this study were analyzed using a simple regression test, the results of which indicated the acceptance of the proposed hypothesis. These results can be seen from the value of the correlation coefficient r = 0.343 or 34.3% with a significance value (P) = 0.000 < 0.01. This shows that there is a very significant relationship between social support and the physiological adjustment of female prisoners.